2010
DOI: 10.1111/j.1600-6143.2009.02966.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Subclinical Inflammation on the Development of Interstitial Fibrosis and Tubular Atrophy in Kidney Transplant Recipients

Abstract: Our aim was to study the impact of subclinical inflammation on the development of interstitial fibrosis and tubular atrophy (IF/TA) on a 1-year protocol biopsy in patients on rapid steroid withdrawal (RSW). A total of 256 patients were classified based on protocol biopsy findings at months 1 or 4. Group 1 is 172 patients with no inflammation, group 2 is 50 patients with subclinical inflammation (SCI), group 3 is 19 patients with subclinical acute rejection (SAR) and group 4 is 15 patients with clinical acute r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
90
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(99 citation statements)
references
References 22 publications
6
90
1
Order By: Relevance
“…Recent studies noted that biopsies with borderline change may not contain the molecular signature associated with rejection (25). These results do not contradict those studies but showed that acute allograft inflammation, perhaps regardless of initiating cause, may have negative long-term consequences for the allograft (12,26). One of the primary goals of these studies was to determine the possible long-term consequences of the histologic changes that follow AR.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies noted that biopsies with borderline change may not contain the molecular signature associated with rejection (25). These results do not contradict those studies but showed that acute allograft inflammation, perhaps regardless of initiating cause, may have negative long-term consequences for the allograft (12,26). One of the primary goals of these studies was to determine the possible long-term consequences of the histologic changes that follow AR.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, early inflammation detected in protocol biopsies predicts progression of renal fibrosis and shorter renal allograft survival (248)(249)(250).…”
Section: Key Molecular Effector Systems and Therapies In Renal Fibrosismentioning
confidence: 99%
“…8 The study by Mengel and associates looked at the significance of nonspecific and minimal cellular infiltrates in renal allograft biopsy and found that the incidence of borderline rejection was 13.9%, where both nonspecific and specific infiltrative histologic categories were identified as predictors of allograft function at 1 and 2 years after transplant. 29 Thus, nonspecific inflammatory infiltrates below Banff threshold may play a role in development of IF/TA and graft function decline in the long-term, as shown in our study.…”
Section: Discussionmentioning
confidence: 62%
“…Heilman and associates performed serial early protocol biopsies and concluded that persistent inflammation diagnosed by protocol biopsy as subclinical inflammation increased the risk of IF/TA at 1 year. 29 In the study by Moreso and associates, protocol biopsies, performed during the first 6 months in stable grafts, were evaluated according to Banff criteria. Cox regression analysis showed that subclinical rejection with fibrosis was an independent predictor of graft survival.…”
Section: Discussionmentioning
confidence: 99%